Nanoparticle Interactions and Molecular Relaxation in PLA/PBAT/Nanoclay Blends. (23rd October 2020) - De Pinho, Maria Norberta; Nofar, M.; Heuzey, M.-C.; Carreau, P.J.; Kamal, M.R.
Abstract: Organo-modified clay nanoparticles were mixed at 1 and 5 wt% concentrations with a molten blend of 75 wt% of polylactide (PLA) and 25 wt% poly[(butylene adipate)-co-terephthalate] (PBAT). Three mixing strategies were used to control the localization of nanoclay. Small amplitude oscillatory shear (SAOS) and stress growth tests were conducted to clarify the nanoclay interactions with the blend components and its effect on the molecular relaxation behavior. SAOS and weighted relaxation spectra properties were determined before and after pre-shearing at a rate of 0.01 s −1 . Molecular relaxation and its characteristics were influenced by PLA degradation, PBAT droplet coalescence, and nanoclay localization.